Biochemistry: the chemical reactions of living cells by David E Metzler - Metzler, David E. (Amsterdam, Academic Press, 2001)
The most comprehensive textbook/reference ever to cover the chemical basis of life, the "Green Bible of Biochemistry" has been a well-respected contribution to the field for more than twenty years. The complex structures that make up cells are described in detail, along with the forces that hold them together, and the chemical reactions that allow for recognition, signaling and movement. There is ample information on the human body, its genome, and the action of muscles, eyes, and the brain. The complete set deals with the natural world, treating the metabolism of bacteria, toxins, antibiotics, specialized compounds made by plants, photosynthesis, luminescence of fireflies, among many other topics.
Includes bibliographical references; ^n23/CSL/E/2003-2004/826^b2003-10-14^mPurchase
Keywords: Biochemistry